2007
DOI: 10.1111/j.1439-0388.2007.00654.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of single nucleotide polymorphism of chicken uncoupling protein gene with muscle and fatness traits

Abstract: Uncoupling proteins (UCPs) are in the mitochondrial inner membrane and belong to the transporter family. The biological function of UCPs is regulating discharge of proton gradient generated by the respiratory chain. As a result, the production of ATP is diminished, and dissipative heat is yielded. The present study was designed to investigate the association of UCP gene with chicken growth and body composition traits. The ninth generation of the broiler lines divergently selected for abdominal fat was used as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 22 publications
0
16
1
Order By: Relevance
“…Many researchers attribute the striking difference to genetic variations, for example, SNP (Liu et al, 2007;Leng et al, 2009;Chen et al, 2012). In the present study, our results showed that PPARγ promoter was differentially methylated in the lean and fat chicken lines and that PPARγ promoter methylation and PPARγ mRNA expression were negative correlated, suggesting DNA methylation variation may also attribute to the chicken fat trait difference in the divergently selected chicken lines.…”
Section: Disussionmentioning
confidence: 46%
See 1 more Smart Citation
“…Many researchers attribute the striking difference to genetic variations, for example, SNP (Liu et al, 2007;Leng et al, 2009;Chen et al, 2012). In the present study, our results showed that PPARγ promoter was differentially methylated in the lean and fat chicken lines and that PPARγ promoter methylation and PPARγ mRNA expression were negative correlated, suggesting DNA methylation variation may also attribute to the chicken fat trait difference in the divergently selected chicken lines.…”
Section: Disussionmentioning
confidence: 46%
“…The Northeast Agricultural University broiler lines divergently selected for abdominal fat content (NEAUHLF) have been established by long-term divergent selection on abdominal fat percentage (AFP) and plasma very low density lipoprotein concentration since 1996 (Liu et al, 2007). The G0 generation of the NEAUHLF both derived from the commercial Arbour Acres grandsire line, which was then divided into 2 lines according to plasma very low density lipoprotein concentration at 7 wk of age.…”
Section: Introductionmentioning
confidence: 99%
“…All the birds were under the same feeding conditions. The information about NEAUHLF and feeding conditions were as previously described (Liu et al 2007).…”
Section: Materials and Methods Experimental Populations And Managementmentioning
confidence: 99%
“…Sherman et al (2008) observed significant association between bovine UCP3 gene mutations and feed efficiency traits (average daily gain, feed conversion ratio and growth efficiency). Recently, some statistically significant associations of the UCP3 gene variants with fatness traits were also found in chicken (Zhao et al, 2006;Liu et al, 2007). Searching for polymorphisms of the porcine UCP3 gene have been already carried out in several European and Chinese native breeds (Li et al, 2005).…”
Section: Discussionmentioning
confidence: 99%